Study on the Mechanical Behavior and Acoustic Emission Properties of Granite under Triaxial Compression. (21st September 2021) - Guo, Jiaqi; Liu, Pengfei; Fan, Junqi; Zhang, Hengyuan
Abstract : To study the rock mechanical behaviors and damage process mechanism of granite samples under triaxial stress, conventional triaxial compression tests were carried out on an RMT-150B rock mechanics testing machine and acoustic emission detector. The test results show that the strength of the granite sample has a good linear relationship with the confining pressure, the cohesion force c of the granite samples is 29.37 MPa, and the internal friction angle is 54.23° by calculation based on the Mohr-Coulomb strength criterion. The larger the initial confining pressure of the rock sample is, the larger the crack initiation stress (σ ci ) and dilatancy stress (σ cd ) of the granite specimen are, the larger the energy values at the crack initiation point and dilatancy point are, and the larger the peak energy storage and energy release rate at the failure are. In the case of a small initial confining pressure, the AE ringdowning counts and the cumulative AE ringing counts increase to their maximum instantaneously at the peak stress point, and the damage of the sample develops rapidly. While the initial confining pressure is high, the AE ringing counts and the cumulative AE ringing counts of the granite specimens increase evenly, and the deformation damage of the granite specimens is slow. Before the crack initiation point, AE signals are mainly low-energy and low-frequency friction-type AE events, while after the dilatation point, AE signals of samples are mainly high-frequency and high-energy fracture-type AE events. The failure mode of granite samples judged by acoustic emission parameters according to the distribution of characteristic values of AE parameters RA and AF is consistent with the reality. The AE b value of the granite sample is large when the confining pressure is low, and there will be a sudden drop, the decrease time is late, and the decrease rate is large. Under the same stress level, the larger the confining pressure is, the larger the damage variable D is.